The Influence of Islamic Work Ethics on Employee Performance with Employee Engagement as Variables Mediation at BMT - Muhammad Khoirun Nasisirin; Zakiyya Ilma Ahmad; Dimyati Dimyati (LPPM STIES BABUSSALAM, 2026)
Study This aim For analyze influence Islamic Work Ethics (IWE) towards performance employee with Employee Engagement as variables mediation at Baitul Maal wat Tamwil (BMT). Competition industry Islamic finance is increasingly strict demanding that BMT not only own superiority in aspect products and services , but also quality source Power human beings who are based on Islamic values . Implementation ethics Islamic work is believed capable form behavior trustworthy , professional , disciplined and responsible work​ answer so that impact on increasing attachment employee to organization as well as push achievement more optimal performance . Study This use approach quantitative with method survey . Population study is all over BMT employees , while sample determined use technique purposive sampling . Data collected through distribution questionnaire use five- point Likert scale and analyzed use Structural Equation Modeling – Partial Least Squares (SEM-PLS) . Variables studied covering Islamic Work Ethics as variables independent , Employee Engagement as variables mediation , and performance employee as variables dependent . Research result show that Islamic Work Ethics influential positive and significant to Employee Engagement and performance employees . In addition , Employee Engagement also has an impact positive to performance employees and proven mediate in a way partial connection between Islamic Work Ethics and Performance employees . Findings This indicates that the more tall implementation ethics Islamic work in organization , increasingly high level​ attachment employees who ultimately increase quality performance individual . Research This give implications practical that strengthening culture Islamic work , internalization mark trustworthiness , honesty , responsibility responsibility and professionalism need become the main strategy in development source Power people in BMT to be able to increase Power competition organization in a way sustainable